2016
DOI: 10.1017/s0022215116008276
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in a patient with chronic rhinosinusitis

Abstract: In patients presenting with refractory chronic rhinosinusitis, ENT surgeons should consider the presence of unusual causative pathogens such as B pseudomallei, particularly in those with recent travel history to Northern Queensland and/or Southeast Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…reported a patient who presented with right-sided facial soft tissue infection, mastoid effusion and temporal lobe cerebritis 5 . Another study reported chronic rhinosinusitis secondary to melioidosis 6 . The usual clinical manifestations of melioidosis can vary, but fall roughly into four classes: asymptomatic carrier in the latent period, prolonged fever without any apparent site of infection, localised infection, and fulminant septicaemia 4…”
Section: Discussionmentioning
confidence: 99%
“…reported a patient who presented with right-sided facial soft tissue infection, mastoid effusion and temporal lobe cerebritis 5 . Another study reported chronic rhinosinusitis secondary to melioidosis 6 . The usual clinical manifestations of melioidosis can vary, but fall roughly into four classes: asymptomatic carrier in the latent period, prolonged fever without any apparent site of infection, localised infection, and fulminant septicaemia 4…”
Section: Discussionmentioning
confidence: 99%
“…Although human-to-human transmission is rare, it has been documented through contact with reproductive fluid, blood or other body fluids of an infected person ( Benoit et al, 2015 ; Singh and Mahmood, 2017 ). Transmissions from humans to animals and vice versa are extremely uncommon and both animals and humans are susceptible to the B. pseudomallei ( Currie, 2015 ; Phillips et al, 2016 ; Mahikul et al, 2019 ). However, we do not incorporate zoonotic infection of humans in this work.…”
Section: Introductionmentioning
confidence: 99%
“…An intensive phase of intravenous antibiotics including ceftazidime (CAZ), imipenem, or meropenem for a minimum of 10-14 days, followed by an eradication phase to prolonged oral trimethoprim-sulfamethoxazole (TMP-SMX) drug for 3-6 months ( Ross et al, 2018 ; Mahikul et al, 2019 ; Fen et al, 2021 ). However, recent studies reported that B. pseudomallei is intrinsically susceptible to several classes of antimicrobial agents that are recommended for treatment of the disease including newer β -lactam antibiotics, especially to all intravenous antibiotics ( Phillips et al, 2016 ; Dutta et al, 2017 ; Sengyee et al, 2017 ; Fen et al, 2021 ). Further, the epidemiology, clinical manifestations and risk factors of the disease are studied in ( Tauran et al, 2015 ; Limmathurotsakul et al, 2016 ; Currie and Kaestli, 2016 ; Hinjoy et al, 2018 ; Wiersinga et al, 2018 ; Chakravorty and Heath, 2019 ).…”
Section: Introductionmentioning
confidence: 99%